Updated Estimates and Mapping for Prevalence of Chagas Disease among Adults, United States - Amanda Irish; Jeffrey D. Whitman; Eva H. Clark; Rachel Marcus; Caryn Bern (Emerging Infectious Diseases, 2022)
We combined American Community Survey data with age-specific Trypanosoma cruzi prevalence derived from US surveys and World Health Organization reports to yield estimates of Chagas disease in the United States, which we mapped at the local level. In addition, we used blood donor data to estimate the relative prevalence of autochthonous T. cruzi infection. Our estimates indicate that 288,000 infected persons, including 57,000 Chagas cardiomyopathy patients and 43,000 infected reproductive-age women, currently live in the United States; 22–108 congenital infections occur annually. We estimated ≈10,000 prevalent cases of locally acquired T. cruzi infection. Mapping shows marked geographic heterogeneity of T. cruzi prevalence and illness. Reliable demographic and geographic data are key to guiding prevention and management of Chagas disease. Population-based surveys in high prevalence areas could improve the evidence base for future estimates. Knowledge of the demographics and geographic distribution of affected persons may aid practitioners in recognizing Chagas disease.